Continuous fabrication of microcapsules with controllable metal covered nanoparticle arrays using droplet microfluidics for localized surface plasmon resonance. Issue 11 (4th May 2017) - Wang, Juan; Jin, Mingliang; Gong, Yingxin; Li, Hao; Wu, Sujuan; Zhang, Zhang; Zhou, Guofu; Shui, Lingling; Eijkel, Jan C. T.; van den Berg, Albert
Abstract : Particle-laden plasmonic microcapsules were fabricated continuously using microfluidic technology, showing high LSPR with high-density "hot-spot" scattering sites. Abstract : The construction of ordered nanoparticle arrays is important for nanophotonics and sensing applications. We report a facile technology for continuous-flow fabrication of particle-laden plasmonic microcapsules (PLPMs) by combining droplet microfluidics, nanoparticle self-assembly and thin film deposition. The metallic hierarchical nanostructures on PLPMs are presented with high-density "hot-spot" scattering sites with the nanoarray pitch and gap distance being controlled by the deposited metal film thickness and nanoparticle size. The noble metal "hot-spots" show high, localized surface plasmon resonance according to the near-field electromagnetic field enhancement. Surface-enhanced Raman scattering (SERS) analytical enhancement factors of >10 7 can be obtained with good reproducibility using 4-methylbenzenethiol (4-MBT) as a probe molecule and Au or Ag as the metal layer. The droplet microfluidics platform enables continuous generation of homogeneous microcapsules with high frequency. This proposed strategy therefore combines advantages from both top-down (creation of microdroplets and deposition of the metal film) and bottom-up (self-assembly of nanoparticles) processes with flexibility in material selection (nanoparticles and polymer) and structure scaling (metal layer thickness, nanoparticle size and microcapsule size). Therefore, it provides a fast and reliable method of producing plasmonic microsensors.